Financial Forecasting Stock Market Forecasting - Batchelor, Roy A.; Dua, Pami. (Cheltenham, UK Edward Elgar Publishing Ltd, 2003)
This two-volume set brings together some of the most significant previously published articles by leading scholars in the field. The volumes investigate various aspects of financial forecasting including the forecasting of earnings, bankruptcy, stock prices, interest rates, exchange rates and risks.
Includes bibliographical references and index
osc 21/6/16
Loans
Keywords: Business Enterprises - Finance; Business Forecating